Assessment of the knowledge, attitudes, and risk perceptions of pharmacy students regarding HIV/AIDS - Mansy, Wael; Syed, Wajid; Babelghaith, Salmeen; Al-Arifi, Mohamed N. (Frontiers in Public Health, 2025)
BackgroundWe recognize AIDS and HIV as serious public health concerns. One of the primary roles of pharmacists is to counsel patients, which is critical in improving patient care outcomes. Therefore, having an adequate understanding of HIV among undergraduates helps them at their practice sites. This study aimed to assess the knowledge, attitudes, and risk perceptions of pharmacy students regarding HIV/AIDS.Methods and materialsWe conducted a cross-sectional study among pharmacy students from December 2023 to April 2024 using structured questionnaires. We collected the data from randomly selected students currently enrolled in the College of Pharmacy at King Saud University in Riyadh, Saudi Arabia. The questionnaire consisted of four parts focusing on students’ demographics, knowledge, attitude, and risk perception toward HIV/AIDS. The data was analyzed using SPSS software, with Chi-squared and Fisher’s tests utilized to determine associations between categorical variables at a significant level of p < 0.05.ResultsA total of 395 pharmacy students completed an online survey. The total mean knowledge score was 6.1 ± 2.8 (Range: 0–13; Median = 6). The majority of students had low knowledge of HIV/AIDS (79.0%) and, a neutral attitude toward HIV/AIDS (61.5%) and only 13.2% of students showed a positive attitude, and 25.3% had a negative attitude toward HIV/AIDS. In addition, 35% of students thought that patients with HIV should be quarantined, 45% of students were concerned about workplace transmission of HIV and their safety on the job, and 41% of them would prefer not to take care of patients with HIV. Furthermore, students aged between 23 and 26 years had a high knowledge level compared to other groups (p < 0.001). Moreover, intern students showed a high level of knowledge of HIV/AIDS compared to other students (p < 0.001). The majority of pharmacy students had a neutral perception of the risk of HIV/AIDS (63.0%). Only 6.1% of pharmacy students reported a positive perception of the risk of HIV/AIDS.ConclusionIn conclusion, there was a dearth of knowledge of HIV/AIDS and neutral attitudes and perceptions of the disease (HIV) among pharmacy students. When compared to other age groups, students between the ages of 23 and 26 had a high degree of knowledge. These findings suggest that specific strategies, such as integrating education on this topic into the pharmacy curriculum and running awareness campaigns for undergraduate students, are necessary.